Effect of Maize Flour and Lactobacillus acidophilus Towards Save Tempe Soybean - Faizah, Laela Noor; Bintari, Siti Harnina; Iswari, Retno Sri (Proceeding International Conference on Science and Engineering, 2020)
Tempe is a traditional Indonesian food product made from soybeans (Glycine max) which is processed through the process of fermentation by mold. Tempe has constraints in its utilization, namely in its short shelf life and has a perishable nature. The purpose of this study was to determine the effect of corn flour on the storability of tempe by the addition of Lactobacillus acidophillus. This research method uses true experimental with two factors. The first factor was Lactobacillus acidophillus 1.5% (v / w) as treatment and 0% (v / w) as control. The second factor is the concentration of corn flour (w / w) respectively 0% (w / w) (T0), 0.4% (w / w) (T1), 0.8% (w / w) (T2) and 1.2% (w / w) (T3). The results showed that the addition of 1.5% Lactobacillus acidophillus and 0.8% corn flour to soybean tempeh was able to increase the shelf life of soy tempeh for a maximum among others 4 days.